2020
DOI: 10.1515/aot-2019-0071
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Ti6Al4V surface properties by combined DLW-DLIP hierarchical micro-nano structuring

Abstract: AbstractThe use of pulsed laser irradiation techniques has proven to be a clearly effective procedure for the achievement of surface properties modification via micro-/nano-structuration, different conceptual approaches having been the subject of research and extensively reported in the literature. Completing the broad spectrum of applications developed mostly involving the generation of structured surfaces (particularly of metallic materials) with specific contact, friction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Alternatively, the creation of hierarchical, periodical structures are a feasible and promising way to combine surface features in the millimeter range with periodic patterns from the DLIP process [9]. Specifically, the combination of direct laser writing (DLW) and DLIP was already investigated to successfully create these kinds of hierarchical, periodical surface features on Ti6Al4V samples [10]. The fundamental mechanisms of DLIP are thought to be the redistribution of molten material.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the creation of hierarchical, periodical structures are a feasible and promising way to combine surface features in the millimeter range with periodic patterns from the DLIP process [9]. Specifically, the combination of direct laser writing (DLW) and DLIP was already investigated to successfully create these kinds of hierarchical, periodical surface features on Ti6Al4V samples [10]. The fundamental mechanisms of DLIP are thought to be the redistribution of molten material.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was also shown that a combination of laser chemical modification and laser texturing followed by chemisorption of low surface energy compounds allows getting the superhydrophobic coatings with exceptional mechanical and chemical properties on top of different substrates [17][18][19][20]. Thus, providing breakthrough results in Metals 2021, 11, 41 2 of 14 materials science [21][22][23][24][25][26][27][28], laser processing of materials has proven to be a quite simple and attractive method for surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Such microstructures enable the realization of unique surface properties such as hydrophobic or antibacterial characteristics as well as optimized tribological properties. [10][11][12] A particular challenge in laser surface functionalization is the adaptability to 3D freeform components, which has become a significant importance for technical applications in recent years. [13] Typical approaches that are being implemented in industry or research laboratories for treated 3D parts are for instance, Computerized Numerical Control (CNC) systems as well as robot systems, which are in some cases limited in accuracy (in particular the robot systems).…”
mentioning
confidence: 99%